Oak pollen infrageneric classification-based winter temperature reconstruction since the marine isotope stage 5 in Southeast China - Yinning Tang; Lu Dai; Fei Gong; Junjie Yu; Jilong Wang; Weijian Zeng; Limi Mao; Zhongjing Cheng; Longbin Sha (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Paleoceanographic evolution of the Chukchi Sea over the past 7600 years inferred from diatom assemblages - Tong Li; Yanguang Liu; Longbin Sha; Tengfei Song; Xinyi Wang; Bin Wu; Jianghu Lan; Dongling Li (Marine Geology, 2025)

Diatoms as indicators of environmental change in coastal areas: a case study in Lianjiang coast of East China Sea - Tong Li; Jihui Zhang; Dongling Li; Chengxu Zhou; Chenxi Liu; Hao Xu; Bing Song; Longbin Sha (Acta Oceanologica Sinica, 2024)

Contrasted changes of sea-surface salinity in the southern and northern Okinawa Trough since the mid-Holocene - Dongling Li; Yanjuan Wu; Marit-Solveig Seidenkrantz; Anne de Vernal; Bangqi Hu; Bing Song; Hui Jiang; Longbin Sha (Global and Planetary Change, 2024)

Surface sediment diatoms in the northern and middle Okinawa Trough and their correlation with environmental variables - Chipeng He; Bin Zhai; Tong Li; Zhilei Sun; Dongling Li; Xilin Zhang; Hao Xu; Xiaodong Yang; Longbin Sha (Journal of Asian Earth Sciences, 2024)

Abrupt fluctuations in North Pacific Intermediate Water modulated changes in deglacial atmospheric CO2 - Yanguang Liu; Yue Qiu; Dongling Li; Antonina V. Artemova; Yuying Zhang; Aleksandr A. Bosin; Sergey A. Gorbarenko; Qingsong Liu; Debo Zhao; Longbin Sha; Yi Zhong (Frontiers in Marine Science, 2022)
As a major reservoir of heat and CO 2 , the Pacific Ocean is an important component of the global climate system, but the nature of its circulation under different climatic conditions remains poorly understood. We present sedimentary records of surface water hydrography and nutrient dynamics from the subarctic Pacific Ocean, with the aim of investigating changes in sea-ice coverage, biological productivity, and sea surface temperature in the subarctic Northwest Pacific since 32 kyr. Our records indicate an enhanced North Pacific surface water stratification from the last glacial to Heinrich Stadial 1, which generally limited the siliceous productivity supply to the surface water. A productivity peak during the Bølling/Allerød warm interval was associated with an increase in the atmospheric p CO 2 , and it was driven by the increased supply of nutrient- and CO 2 -rich waters. This process can be attributed to the collapse of the North Pacific Intermediate Water formation at the onset of the Bølling/Allerød interstadial. Moreover, a northward shift of the westerly winds and the gyre boundary could have modulated the expansion of the subpolar gyre, driving changes in poleward heat transport, biogeochemistry, and the hydroclimate of the North Pacific. Our results are consistent with modern evidence for a northward shift of the westerlies in response to global warming, which will likely result in CO 2 outgassing from the subarctic Pacific Ocean in the future.

Sedimentary Environmental Evolution of the Western Taiwan Shoal Area since the Late Pleistocene - Chipeng He; Longbin Sha; Dongbo Zhao; Lu Dai; Zheng Li; Jiabing Tang; Xianfu Li; Dongling Li (Journal of Marine Science and Engineering, 2021)
A new pollen analysis and major and trace element contents were conducted on a 40 m long gravity core recovered from the Taiwan Shoal (sand ridges), south of the Taiwan Strait, beginning in the Late Pleistocene. The changes in the pollen assemblage and concentration represent the climate change around the Taiwan Shoal and the strength of the Zhe-Min Coastal Current, whereas variations in major and trace element contents can imply the source of the sediments in the Taiwan Shoal, which are correlated with the rise or fall of the sea level with increased marine dinoflagellate cysts. The interval of 40–30 m was characterized by high pollen and spore concentrations, and evergreen Quercus was dominant taxon, which indicates a warm sedimentary environment, and the surrounding area of the Taiwan Shoal were covered by a tropical and subtropical broad-leaved forest. There were no pollen and spores from 30–24 m, which indicates a strong hydrodynamic sedimentary environment, and most of the Taiwan Shoal might have been experience subaerial exposure. The interval of 24–17 m was characterized by the reappearance of pollen and spores, as well as marine dinoflagellate cysts and foraminifera, suggesting the climate was warm and wet in the study area and an apparent marine sedimentary environment with relatively high sea level. Deciduous Quercus dominated the interval of 17–12 m, which indicated that the climate was relatively cool, corresponding to the end of Marine isotope stages3 (MIS3) to the Last Glacial Maximum accompanied by weathering and denudation. Above 12 m, the low pollen concentration with increased marine dinoflagellate cysts and foraminifera abundance suggested a marine sedimentary environment in the Taiwan Shoal. The high concentrations in Pinus corresponds to Holocene high sea level.

Biogenic silica concentration as a marine primary productivity proxy in the Holsteinsborg Dyb, West Greenland, during the last millennium - Longbin Sha; Dongling Li; Yanguang Liu; Bin Wu; Yanni Wu; Karen Luise Knudsen; Zhongqiao Li; Hao Xu (Acta Oceanologica Sinica, 2020)

Palaeo-sea-ice changes on the North Icelandic shelf during the last millennium: Evidence from diatom records - LongBin Sha; Hui Jiang; YanGuang Liu; MeiXun Zhao; DongLing Li; ZhenLou Chen; Yun Zhao (Science China Earth Sciences, 2015)

A diatom‐based reconstruction of summer sea‐surface salinity in the Southern Okinawa Trough, East China Sea, over the last millennium - Dongling Li; Mads Faurschou Knudsen; Hui Jiang; Jesper Olsen; Meixun Zhao; Tiegang Li; Karen Luise Knudsen; Marit‐Solveig Seidenkrantz; Longbin Sha (Journal of Quaternary Science, 2012)
A high‐resolution diatom record from site MD05‐2908 in the Southern Okinawa Trough, East China Sea, reveals pronounced multidecadal‐ to centennial‐scale palaeoceanographic changes throughout the last millennium. Summer sea‐surface salinity (SSS) was reconstructed using a weighted averaging partial least squares diatom‐based training set. The reconstructed SSS shows slightly decreasing values during the period AD 905–1930 with considerable fluctuations superimposed on this general trend. Relatively high‐salinity conditions during the interval AD 905–1450 probably suggest a low flood frequency in north‐eastern Taiwan. Furthermore, the high SSS values are associated with a strong and stable influence of the Kuroshio Current on the Southern Okinawa Trough during the Medieval Climate Anomaly. The period AD 1450–1930 is characterized by three low‐salinity intervals (AD 1450–1500, AD 1625–1725 and AD 1770–1880) separated by periods of relatively high salinity. The low SSS intervals indicate increased freshwater discharge into the Southern Okinawa Trough during the Little Ice Age, probably as a result of higher flood frequencies in north‐eastern Taiwan. Spectral and wavelet analyses suggest that this pattern was linked to multidecadal variations in summer SSS, presumably associated with the Pacific Decadal Oscillation. Copyright © 2012 John Wiley & Sons, Ltd.

Depositional environment in the southern Ulleung Basin, East Sea (Sea of Japan), during the last 48 000 years - Yanguang Liu; Longbin Sha; Xuefa Shi; Bong-Chool Suk; Chaoxin Li; Kunshan Wang; Xiaoyan Li (Acta Oceanologica Sinica, 2010)